Acceptance of edible insects: a study in the Colombian context - Carlos Osorio-Andrade; Juan Manuel Candelo-Viáfara; Carlos Arango-Pastrana (Brazilian Journal of Food Technology)
Abstract This study investigated the factors influencing the adoption of insect-based foods in Colombia. A survey was administered to 489 participants, and the data were analyzed using structural equation modeling. The results indicated that attitudes toward insects and perceived benefits may be positively correlated with consumption intentions, whereas food neophobia, food-related health concerns, and older age negatively affected acceptance. Notably, variables such as environmental awareness, education level, and socioeconomic stratum did not exhibit significant relationships. The study could conclude that the acceptance of edible insects in Colombia is primarily driven by psychological and perceptual factors rather than socioeconomic or ideological variables. The originality of this research lies in its focus on the previously underexplored Latin American context and the inclusion of novel variables such as political ideology. The findings underscore the need for targeted promotional strategies aimed at altering perceptions and attitudes, especially among younger demographics, to foster the adoption of this sustainable food alternative in Colombia and Latin America.